Risks of Catastrophic Derailments Involving the Release of Hazardous Materials - Glickman, Theodore S.; Rosenfield, Donald B. (Management Science, 1984)
Models are formulated and computed to assess the risks of hazardous materials releases in train derailments in terms of: the probability of any number of fatalities in an accident, the probability of any total number of fatalities from all the accidents in a year, and the frequency of accidents which result in any given number of fatalities. These functions are evaluated using data bases and analytical methods which provide estimates of exposure levels (traffic volumes, track conditions and population densities), spill occurrence and spill size probabilities, and fatal spill impacts (the size of the lethal area in any given accident scenario). Despite the sparsity of historical data, this methodology enables us to express the potential for catastrophic occurrences in quantitative terms, to compare these numbers with estimates of other risks, and to examine the effects of selective variations in the model inputs.